Sex steroid priming in short stature children unresponsive to GH stimulation tests: Why, who, when and how - Partenope, Cristina; Galazzi, Elena; Albanese, Assunta; Bellone, Simonetta; Rabbone, Ivana; Persani, Luca (Frontiers in Endocrinology, 2022)
Despite decades of experience, the diagnosis of growth hormone deficiency (GHD) remains challenging, especially in peripubertal children. Failure to respond to GH stimulation tests (GHSTs) is needed to confirm GHD, but long-standing controversies regarding the number of tests needed and the interpretation of GH peaks are still a matter of debate worldwide. Diagnostic workup is even more problematic in short children with slow growth and delayed sexual development: they often exhibit low GH peaks under GHST, which often normalize as puberty progresses. Consequently, this transient suboptimal response to GHST may result in GH overtreatment, with both health and economic concerns. Because of the complex and close link between GH axis and sex steroids, the use of sex steroid priming prior to GHST might be helpful in peripubertal setting. However, its use is still controversial. There is no consensus regarding patient selection, timing, dosage preparation and administration of sex steroids. In this review, we aim to overview the use of sex steroid priming in clinical practice, highlighting the need to develop appropriate guidelines in order to overcome diagnostic pitfalls in peripubertal age.